Effect of Optimum Utilization of Silica Fume and Eggshell Ash to the Engineering Properties of Expansive Soil - Muzamir, Hasan; Muhammad Syamsul Imran, Zaini; Ling, Sin Yie; Khairil Azman, Masri; Putra Jaya, Ramadhansyah; Hyodo, Masayuki; Winter, Michael James (Elsevier Ltd, 2021)
The utilization of substance stabilizer in soil improvement can diminish the obstructive ecological effect in the development business, and respond as the soil stabilizers to the kaolin clay soils. In any case, the improvement of kaolin clay stays a test because of the significant expense and non-eco-accommodating materials like concrete and lime. This examination exhibits the capacity of SF in the mix with ESA in stabilizing the delicate kaolin clay soils, by means of particle size distribution (PSD), specific gravity, Atterberg limits, compaction parameters and undrained shear strength (USS) parameters. Its impact on the undrained shear strength upgrade was concentrated through the concrete substitution material in kaolin clay soil at the replacement degree of 2%, 4% and 6% (by dry weight of kaolin clay soil) of SF and ESA replacements of 3%, 6% and 9% (by dry weight of kaolin clay and SF content). The consideration of SF with ESA shows a lower specific gravity (4.9% decrease), lower plasticity index (PI) (48.4% decrease), diminished maximum dry density (MDD) (5.5% decrease), expanded in optimum moisture content (OMC) (8.7% increase), and higher USS (68.8%) when contrasted with the untreated kaolin clay soils and those treated with SF. The blends of SF and ESA as soil adjustment specialists effectively upgrade the undrained shear strength of the kaolin clay soils up to 68.8% strength improvement with the best percentage of 6% SF and 6% ESA for optimum enhancement of the expansive soil, which minimizing the expenses and as an eco-accommodating materials in soil improvement.